Influence of systematic standard and Nordic walking training on exercise tolerance and body weight components in women over 55 years of age - Knappova, Vera; Dorota, Kopeć; Anna, Witkowska; Kavalirova, Gabriela; Zbigniew, Nowak; Gabryś, Tomasz; Agata, Nowak-Lis (Frontiers in Sports and Active Living, 2025)
BackgroundThe most physiological form of movement of human body is walking. The aim of the study was to assess the changes before and after workout programme in body mass components and exercise tolerance in women above 55 years of age, both in standard walking (March training) and walking with poles (Nordic Walking).Material and methods77 (55–64 years) women were divided into two groups: I - 37 women, participating in the marching training. II - 40 women participating in the Nordic Walking training. CPET, and body composition analysis were performed in each of the participants before and after workout program.ResultsSignificant changes in VO2peak, both in standard walking group and Nordic walking, distance and test duration were observed. The evaluation of body composition Standard and Nordic Walking groups concerned statistically significant changes in the same indicators at the same level of significance: fat content (%), water content inside and outside the cell (%). In Nordic walking group there where some significant correlations between the changes in body fat (%), body weight, visceral obesity and fitness scores, changes in metabolic cost associated with the exercise test, changes in body fat (%) content and increase in the duration of the exercise test, as well as changes in body fat (%) content and increase in the distance of the test.